UPAYA MENUMBUHKAN JIWA BERWIRAUSAHA PADA MAHASISWA AKADEMI KESEJAHTERAAN IBU KARTINI - Susanti, Agus (Journal of Innovation Research and Knowledge, 2024)
Universities have an obligation to change the mindset of students from job seekers to job creators, so universities must strive to foster an entrepreneurial spirit in students. The aim of the research is to determine efforts to foster the entrepreneurial spirit of Mrs. Kartini's AKS students. The type of research is qualitative research. Research data comes from primary data and secondary data. To obtain primary data, this was done through student interviews and observations. Meanwhile, secondary data was obtained through primary data processing and library research originating from scientific journal articles, research notes and related reference sources. The research subjects were AKS students, Mrs. Kartini, Cosmetology Study Program. Interviews were conducted with 7 fourth and sixth semester students who had taken the Entrepreneurship course. The analysis used is descriptive qualitative. The obstacles experienced by students are lack of self-confidence, business capital, time management, and lack of business experience. Efforts that can be made to foster an entrepreneurial spirit in students are by holding student creativity and innovation competitions, so that students not only understand theory but can put it into practice and also come up with business iNarasumber Ds. Providing motivation and mentoring in cultivating an entrepreneurial spirit. Providing mentoring and business incubators. Develop a curriculum that is integrated with entrepreneurship development. Providing technology training facilities that support business iNarasumber Ds